THE DEVELOPMENT OF EFFECTIVE CONCENTRATE OF THE FILLER ON THE BASIS OF POLYETHYLENE AND ULTRAFINE SILICON DIOXIDE FOR PLASTIC PACKAGING BUILDING MATERIALS - Galina Mikhailovna Danilova-Volkovskaya; Valery Yurievna Shimlovskaya (Современная наука и инновации, 2022)
The article describes the purpose of the research - development concentrates of fillers based on polyeth-ylene and silicon dioxide, which presents the first results of application of the concentrate for the production of three-layer corrugated exhibition of polyethylene film with a thickness of 50 μm with improved technological and operational indicators.